HTLV-I Antibody Status in Hemophilia Patients Treated with Factor Concentrates Prepared from U.S. Plasma Sources and in Hemophilia Patients with AIDS - Chorba, T L; Jason, J M; Ramsey, R B; Lechner, K; Pabinger-Fasching, I; Kalyanaraman, V S; McDougal, J S; Cabradilla, C D; Tregillus, L C; Lawrence, D N; Evatt, B L (Thrombosis and Haemostasis, 1985)
Serum samples from 85 Austrian hemophilia patients treated with lyophilized factor concentrates prepared from U.S. plasma sources, 24 hemophilia patients from Georgia on a home therapy program with factor concentrates, and 10 U.S. hemophilia patients with acquired immunodeficiency syndrome (AIDS) were analyzed by two different methods for the presence of antibodies to the major internal antigen of human T-cell leukemia virus I (HTLV-I) p24. All but one, a Georgia sample, were negative. The absence of antibody to HTLV-I p24 in the serum of European hemophilia patients, of U.S. hemophilia patients with no symptoms of AIDS, and of U.S. hemophilia patients with AIDS is interpreted as an indication of the lack of ready transmissibility of HTLV-I in lyophilized factor concentrates.
Keywords: HTLV; Hemophilia; Factor concentrates